The psychiatric vulnerability gene CACNA1C and its sex-specific relationship with personality traits, resilience factors and depressive symptoms in the general population - Strohmaier, Jana; Amelang, Manfred; Witt, Stephanie; Nieratschker, Vanessa; Meier, Sabrina; Wüst, Stefan; Frank, Josef; Loerbroks, Adrian; Rietschel, Marcella; Stürmer, Til; Schulze, Thomas G. (Molecular psychiatry, 2013)
Genome-wide association studies have reported an association between the A-allele of rs1006737 within CACNA1C and affective disorders and schizophrenia. The aim of the present study was to investigate the relationship between rs1006737 and established and potential endophenotypes for these disorders in a population-based cohort of 3793 subjects, using an analytical method designed to assess a previously reported sex-specific effect of CACNA1C. The investigated endophenotypes included personality traits and resilience factors. At 10-year follow-up, subjects were screened for depressive symptoms. All subjects were genotyped for rs1006737. The direction of the effect and mode of inheritance of rs1006737 differed between the sexes. In men, the A-allele was associated with higher emotional lability and lower resilience, that is, lower sense of coherence (P=0.021), lower perceived social support (P=0.018), lower dispositional optimism (P=0.032) and more depressive symptoms at follow-up (P=0.007). In women, the A-allele was associated with lower emotional lability and stronger resilience, that is, higher sense of coherence (P=0.00028), higher perceived social support (P=0.010), lower neuroticism (P=0.022) and fewer depressive symptoms at follow-up (P=0.035). After conservative Bonferroni correction for 32 tests, results only remained significant for sense of coherence in women (P=0.009). These results suggest that CACNA1C is involved in the genetic architecture of endophenotypes for affective disorders and schizophrenia, and that it shows a distinct sex-specific effect. Comprehensive phenotype characterization in case-control samples and the general population, as well as an adequate modeling of sex-specific genetic effects, may be warranted to elucidate the pathogenetic mechanisms conferred by robustly identified susceptibility genes.
Published online 5 June 2012
Gesehen am 21.08.2020